LEGAL CONSEQUENCES OF ACCOUNTABILITY PRINCIPLES AND COMPANY TRANSPARENCY VIOLATION TOWARD COMPANY SHAREHOLDERS - Yulianti, Nina Dwi (Awang Long Law Review, 2023)
This study aims to analyze Decision 1028/Pid.Sus/2020/Pn.Jkt.Sel regarding the Actions of the Former Directors of PT. Tiga Pilar Sejahtera Food Tbk in terms of inflating financial reports that cause losses for investors. In addition, the study will examine how GCG violations—particularly those involving accountability and transparency—were carried out by the former directors of PT. Tiga Pilar Sejahtera Food Tbk and how they affected the company’s stockholders. Legal normative research is the methodology employed. The study’s findings demonstrate that, on their own, internal corporate rules like the GCG guidelines of the company and the application of relevant laws and regulations to ensure that the principles of transparency and accountability are upheld are insufficient to prevent violations. Additionally, the two former Directors of PT. Tiga Pilar Sejahtera Food Tbk’s fraud on the financial statements due to their violation of the principles of transparency and accountability caused a significant price decrease for the company’s shareholders.